PENGEMBANGAN ASESMEN DIAGNOSTIK MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Wiwik Okta Susilawati; Sonia Yulia Friska; Rohmawanti (STKIP Subang, 2023)
This research is motivated by the use of diagnostic assessments that are not optimally taught to students. This study aims to produce a valid and practical diagnostic assessment of the Pancasila Education subject for class IV in the Merdeka Curriculum at SDN 01 Sitiung. The type of research used is research and development. The development model used is the ADDIE model. Based on the results of the validity test of the four expert validators, the language validation score was 90%, the material validation score was 91,42%, the graphic validation score was 88% and the item validation score was 86%. So that the average percentage data obtained is 88,85% with a very valid category. The results of the practicality test from the assessment of the response of class IV teachers obtained 93%, from the assessment of the response of the school principal, it obtained 92% and from the assessment of the response of the driving teacher, it obtained 92%. So that the average percentage is 92% with a very practical category.